Memory and aging: What is the real impact of age? - Espirito-Santo, Helena (2016)
Background & Goals: Memory impairment is one of the types of cognitive impairment that most affects the elderly. Age is considered one of the major factors in memory impairment, including by the elderly themselves. Research has shown that there are other factors affecting the memory of elderly persons. It remains, however, unclear what is the real impact of age in memory when controlling the influence of other variables. Thus, this study aims to analyze the impact of age on memory functioning of elderly persons and check if the potential impact remains when controlling the role of other variables (sex, education, profession, marital status, residential status, and clinical situation). Method: The global sample comprised 1126 subjects (283 men and 843 women, 226 residents in the community, and 900 institutionalized elderly) aged from 60 to 100 years. The assessment included items from the Mini-Mental State Examination (working memory), the Montreal Cognitive Assessment factor (verbal declarative memory), and Rey-Osterrieth Complex Figure (visuospatial memory). Results: Overall, age, education, profession, marital, residential, and clinical condition have differently influenced memory, depending on the type of memory. The hierarchical regression analysis showed that age is a predictive factor in all types of memory. However, other predictors have emerged with higher regression coefficients compared to age, according to the type of memory (except in working memory). Conclusions: Age, education, and profession influence memory, as well as factors that potentially stimulate cognitively and socially (like having a partner and living in the community). The results indicate the importance of intervening, especially among institutionalized elderly, older, unmarried, with low education, and manual profession.